Morphogenetic and population structure of two species marine bivalve (Ostreidae: Saccostrea cucullata and Crassostrea iredalei) in Aceh, Indonesia - MUTIA RAMADHANIATY; ISDRAJAD SETYOBUDIANDI; HAWIS H. MADDUPPA (Society for Indonesian Biodiversity, 2018)
Ramadhaniaty M, Setyobudiandi I, Madduppa HH. 2018. Morphogenetic and population structure of two species marine bivalve (Ostreidae: Saccostrea cucullata and Crassostrea iredalei) in Aceh, Indonesia. Biodiversitas 19: 978-988. Oysters (Family Ostreidae) are mollusks, with high levels of phenotypic plasticity and wide geographic distribution. Oysters are a challenging group for morphological identification and genetic populations study. Saccostrea cucullata and Crassostrea iredalei are oysters from bivalve class that lives in the intertidal area and mangrove ecosystem. To clarify the morphology, genetic diversity and population structure of the two forms of S. cucullata and C. iredalei, we collected and studied oysters from three locations along the coastal region of Aceh by using morphometric method and 16 S mtDNA sequences analysis. We also added more oysters sequences from China, Japan, and Thailand to determine the connectivity between all populations. Morphometric characteristics of the oyster showed a negative allometric growth pattern, which means the rate of length gain is faster than that of the weight gain. The genetic distance from S. cucullata was 0.003-0.004 (Fst = 0.708) and C. iredalei was 0.000 (Fst = 0.971). The long genetic distance and high fixation index (Fst) in the oysters population are caused by the close geographical distance of the species in the three populations. The haplotype diversity value from S. cucullata and C. iredalei were 20 and 3, respectively. The haplotype showed the connectivity among the oyster populations which indicated by the gene flow pattern. The gene flow was affected by geographical distance and environmental complexity.